PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN, DAN PERSEPSI KEAMANAN TERHADAP KEPUTUSAN PENGGUNAAN APLIKASI PEMBAYARAN DIGITAL (E-WALLET) - muhammad Alfaris (Jurnal Mahasiswa Akuntansi Samudra, 2023)
Technology is a tool that facilitates all kinds of daily activities. Increasingly advanced technological developments encourage community activities in increasing the need for goods and services. Technological developments also make it easier for users to make purchases using a cashless transaction payment system. The development of technology makes the number of consumers increase so that technology becomes an important part of the non-cash payment feature system. in the digital economy in using electronic e-wallets. This study uses the literature study method, by conducting library data collection methods from various sources that are relevant to the issues studied, both in the form of written sources. In this study, various reference sources regarding relevant theories include the AHP method, TOPSIS method, Decision Support System (SPK), skin care, USE Questionnaire, and Likert scale. Sources and references are taken and searched through books, journals, articles, to the internet. This literature study aims as a theoretical basis to strengthen the problem solving in this research.